Neuropsycholinguistic Study: The Influence of Speech Production on Language Acquisition in Children - M. Fakhrurrozy K.; Harahap, Rosmawaty (PT Inovasi Pratama Internasional, 2024)
This research aims to understand the influence of speech production on language acquisition in children. This research uses qualitative methods with documentation and interview techniques to collect data. The research results show that speech production has a significant influence on language acquisition in children. Children who have good speech production skills tend to have better language skills too. This research contributes to the understanding of how speech production influences language acquisition in children. This can help parents, teachers and therapists develop appropriate intervention programs to help children with language learning difficulties.